Writing skills among Norwegian Americans – what may their letters reveal? - Hjelde, Arnstein; Bjørke, Camilla (Bergen Language and Linguistics Studies, 2025)
The Norwegian emigration to America created an urgent need for literacy among emigrants; for the first time, writing letters became an important skill for preserving ties with the family in the “old country”. However, few of the early emigrants were trained for this task even if they had been through a compulsory schooling. The school in the first half of the 19th century was closely linked to church, with the aim of preparing pupils for confirmation. Thus, the curriculum focused on reading and memorizing religious texts, but not on writing. However, towards the end of the 1800s, educational reforms in Norway had introduced a broader curriculum, including writing, which improved the literacy of subsequent emigrants. This study examines and compares certain linguistic features in letters from two periods: the early letters (prior to the Civil War) and those written in the early 1900s. The early letters are written by emigrants who had learned to read in school, but not to write, and thereby had to compensate this lack by drawing on other experiences, like what they had learned by reading religious texts. The more recent letters were written by emigrants who had learned to write in the secularized school in Norway or by second generation immigrants, who indeed had learned to write English, but were not sufficiently trained in utilizing this skill on the heritage language. The preliminary analysis reveals shifts in writing practices, including a decline in topicalization and changes in possessive structures over time. Early letters predominantly featured prenominal possessives and minimal compositional definiteness, while later letters showed an increase in both these features, which can be interpreted as if the spoken variety gained more importance as a norm for writing over the investigated time span.